Effect of ethephon ripening and peeling on quality of fresh walnut during freezing storage - WU Xiao-hua; CHEN Bai; LI Ming-ze; ZHANG Rui; FENG Ji-hu (Shipin yu jixie, 2022)
Objective: To evaluate the feasibility of the production of ethephon in the freezing thawing and fresh keeping of fresh walnut, and to provide theoretical basis and technical support for fresh walnut freezing thawing and fresh keeping technology system. Methods: The late fruiting walnut variety 'Qingxiang' from Longnan county of Gansu province was used as the experimental material, and then the green walnut was picked by hand and then peeled by Ethephon. Meanwhile, the artificial peeling was used as the control （CK）. The fresh walnut was peeled and stored in a constant temperature freezer with temperature of -7~-5 ℃ and humidity of 85%~95%, the effects of ethephon on sensory quality （seed shell color, seed coat color, seed coat browning index, peeling difficulty and seed kernel flavor）, nutritional quality （water content, total fat content） and oil quality （acid value, iodine value, peroxide value and saponification value） of fresh walnut kernel after freezing thawing were studied. Results: Under the conditions of -7~-5 ℃ frozen storage, Ethrel accelerated the browning rate of peeled fresh kernels in the early stage of frozen storage to a certain extent. After 10 months of frozen storage, the scores of shell color, shell color and kernel flavor were 73.48, 74.56 and 77.26, respectively; The kernel water content, total fat content, acid value, iodine value, peroxide value and saponification value were 22.07%, 49.74%, 0.62 mg/g, 145.31 g/100 g, 3.62 meq/kg and 169.53 mg/g, respectively. There was no significant difference compared with the artificial peeled fresh walnut, which could maintain better flavor and nutritional quality. Conclusion: Ethephon accelerated ripening and peeling had no adverse effect on the quality of fresh walnut after freezing thawing. Ethephon could be used in the pretreatment process of fresh walnut frozen storage.